Concepts of Social Welfare and Citizenship as Guidelines of Public Policy - Jokubaitis, Alvydas; Norkus, Zenonas (Sociologija. Mintis ir veiksmas, 2006)
The article provides a metatheoretical analysis of the ideas of social welfare and public policy goals recorded in the essential documents of the contemporary Lithuanian state. Two methods are applied: a hermeneutical-historical analysis of legal and political texts, and that of rational reconstruction, which is used to infer metatheoretical foundations of the value and normative statements expressed in these texts. The most important among them is the Constitution of the Republic of Lithuania which is considered as social contract constituting Lithuanian political nation. Three layers of the citizenship rights – civil rights, political rights, and social rights – are identified in the body of Constitution. They are considered as historically contingent local reflections of the different epochs of the history of Western world, claiming universal significance for some of its outcomes. Two alternative – an individualistic and a holistic one – concepts of social welfare together with methodologies of its measurement are discussed as alternative resources to provide philosophical-sociological metatheory for the text of Constitution. This combination of the methods referred to above is applied also for the analysis of the strategical long-term planning documents elaborated by the Lithuanian political parties and Lithuanian government. This analysis is used to advance the proposal to use the concept of citizenship rent to describe the paramount goal of the Lithuanian national policy under conditions of eurointegration and globalization. The „citizenship rent“ is defined as surplus life chances conditional on the membership in the political nation and due to its comparative advantages that can be augmented by means of public policy.
Keywords: constitution of Lithuanian Republic; societal contract; civil rights; political rights; social rights; individualism; holism